Blogging to Counter Epistemic Injustice: Trans disabled digital micro-resistance - Sarah Cavar; Alexandre Baril (Disability Studies Quarterly, 2021)
As part of a larger research project on the intersections between transness, disability, cisgenderism (also called transphobia), and ableism/sanism, this article presents the results of a three-month netnography of blog posts made between 2013 and 2019 by selected Tumblr and off-Tumblr blogs authored by people identifying as both trans and disabled. Mobilizing a theoretical framework that combines trans and disability/crip/Mad theory and the notion of epistemic injustice, we highlight the unique possibilities of community building, connection, identity formation, and micro-practices of resistance in trans disabled digital communities. Trans disabled bloggers counter epistemic injustice by speaking back, reclaiming space, and responding to the cisgenderist and ableist/sanist micro-aggressions they experience in their daily lives. This exploration of trans disabled bloggers' micro-activism is divided into four parts. After reviewing the literature in the emerging field of trans disability studies in the first part, the second and third parts present our theoretical and methodological frameworks. Findings are presented and discussed in the three subsections of the fourth part, which delves deeper into our typology of three interrelated genres of trans disabled blog posts: informational, testimonial, and activist. As their names suggest, these genres aim respectively to: 1) inform other trans disabled internet users of identificatory possibilities; 2) testify about bloggers' lived experiences; and 3) advocate for trans disabled people through appeals to users both within and outside trans and disabled communities.
Keywords: Trans people; disabled/Mad people; gender identity; cisgenderism; ableism; sanism; netnography; blogs; micro-activism